Synthesis and Evaluation of Some Substituted 2-Arylamino Coumarinyl Thiazoles as Potential NSAIDs - Venugopala, K.N.; Jayashree, B.S.; Attimarad, Mahesh (Asian Journal of Chemistry, 2016)
Substituted 2'-arylamino-4'-(3-coumarinyl) thiazoles (5a-j) and 2'-arylamino-4'-(6-bromo-3-coumarinyl) thiazoles (5k-v) were synthesized by the condensation of respective 3-bromoacetylcoumarins with thiourea and substituted phenylthioureas. Finally the compounds were characterized by spectral data and screened for their analgesic and anti-inflammatory activities. Some of these compounds exhibited promising activity.